Mapa conceitual para a representação do conhecimento sobre os princípios da homeopatia aplicados ao cultivo de morango - Maristela Sanches Lima Mesquita (2023)
The Concept Map has the function of presenting semantically structured concepts, representing the knowledge of a given domain in a graphically visual structure. This representation should highlight the relationships established among the concepts, which are communicated by labels, enabling shared understanding in a discourse community. One of the recurring problems in every domain refers to terminological ambiguities, when there is a rupture in the conceptual consensus, occurring noise in the communication in the information systems, which impairs the retrieval of relevant information to the user. In the domain of the Science of Homeopathy, recognized as a medical specialty by the Brazilian Federal Council of Medicine in 1980, these ambiguities have been one of the impediments to the recognition of homeopathy as valid knowledge and to consolidating its therapeutic principles. Given this problem, this study proposes to elaborate a Conceptual Map to represent the homeopathic knowledge (processes and therapeutic applications) in the scope of the acology of high dilutions applied in Agronomy, with a focus on phyto techny, in particular, used in the culture of strawberry (Fragaria x ananassa Duch.). The theoretical and methodological foundations focus on inputs about the organization of knowledge and encompass concept map construction methodologies and Concept Theory, which supports conceptual modeling. The methodology has an applied nature, with exploratory and descriptive objectives, using a qualitative approach of data interpretation that refers to a case study. The methodological procedures include the procedures of Gonçalves (2010), Moraes (2014) and Moresi et al. (2019) for the modeling of the domain and for the construction of the concept map, considering that together they contemplate the necessary actions for the achievement of the outlined objectives. For the semantic refinement of the relationships, the proposal of Maculan (2015) and Oliveira (2018) was used. For the graphical construction of the concept map, the yEd Graph Editor software was used. The results showed that concept maps have elements that characterize them as a system of knowledge organization, especially regarding the systematized structuring of concepts and the explicitness of the semantic relationships that occur between these concepts. This structure forms a conceptual system that allowed the representation of homeopathic knowledge, regarding the use of high dilutions in strawberry (Fragaria x ananassa Duch.) cultivation. It can be said that, with this, the concepts have been clarified, making it possible to share a consensual understanding of the theme.